A Bibliometric Analysis of the Journal of Religion and Health: Sixty Years of Publication (1961–2021) - Carey, Lindsay B. (Journal of religion and health, 2023)
In 1961, the Journal of Religion and Health (JORH) commenced publishing articles that examined modern religious and spiritual philosophy in relation to psychology and health. The year 2021 marked the 60th anniversary of the founding of JORH. This research paper retrospectively analyses the journal’s content. It provides insight into JORH’s publication trends, citation records, prominent themes, authors’ collaboration and its aggregate contribution to the field of religion and health. Over time, the number of publications, citations and downloads of JORH articles have substantially increased, as has the journals prominence and diverse contributions to the study of religion, spirituality and health.